ANALISIS KEPUASAN MASYARAKAT PADA PELAYANAN PT. SUMEKAR SUMENEP - Umlatun Hasanah; Miftahol Arifin (Journal MISSY (Management and Business Strategy), 2022)
This article was written with the aim of knowing community satisfaction with the services provided by PT Sumekar on the Kalianget-Kangean cross.The type of research used in this study uses qualitative research methods, which include observation, interviews and documentation. The technique used in determining the informants and respondents is using purposive sampling which is a technique for taking data sources with certain considerations. The results of this study indicate that to provide community satisfaction with PT Sumekar's services, namely providing physical evidence (facilities and infrastructure) in the form of DBS I and DBS III ships. As for PT. Sumekar to improve the performance of its services, which can be done by having a reliable ability to work and provide a good response, guarantee or certainty for passengers and an empathetic attitude towards the community or passengers.